Implementation of Kaizen Culture in Occupational Health and Safety (OHS) at PT. Automotive Manufacturing Indonesia with the 5S Method - Alfatonah, Zahrotul; Wardani, Zaqki Maulana; Adriansyah, Aden Panca; Salaf, Fatwa Aulia; Prastyo, Yudi (Lentera Ilmu Nusantara, 2024)
To improve efficiency, quality and safety in the work environment, the application of Kaizen culture is indispensable. This study aims to analyze the application of Kaizen culture in OHS with the 5S method, namely Seiri (Sort), Seiton (Set in Order), Seiso (Shine), Seiketsu (Standardize), and Shitsuke (Sustain) at PT. Indonesian Automotive Manufacturing. The research method uses a qualitative approach with data collected through direct observation and interviews of workers. The results showed that there were still shortcomings in undergoing OHS at PT Automotive Manufacturing Indonesia. It is necessary to increase workers' awareness of the importance of OHS again in order to reduce the risk of work accidents, create a clean and orderly work environment.